1999
DOI: 10.1046/j.1365-2672.1999.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular differences distinguish clonal lineages within East African populations of Fusarium oxysporum f.sp. cubense

Abstract: E .M . L O DW IG , P. D. B RI DG E , M .A . RU TH E RF OR D , J . K U NG 'U A ND P. J EF FR I ES . 1999. Molecular approaches for the assessment of intraspecific diversity within an economically important plant pathogen were compared with traditional physiological methods (vegetative compatibility testing). The vegetative compatibility groups (VCGs) of 14 isolates of Fusarium oxysporum f.sp. cubense (FOC) from Kenya were first assessed using nitrate non-utilizing mutants. Nine of these isolates, from different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The widespread occurrence could be due to human dispersal of planting material. VCG 01220, for example, which is commonly found throughout the Indian subcontinent, is also found in East and Central Africa (ECA) [ 65 ], a region with a well-established relationship with India. Fusarium wilt was discovered in ECA when a large community of Indian emigrants settled in the area soon after World War II ended [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The widespread occurrence could be due to human dispersal of planting material. VCG 01220, for example, which is commonly found throughout the Indian subcontinent, is also found in East and Central Africa (ECA) [ 65 ], a region with a well-established relationship with India. Fusarium wilt was discovered in ECA when a large community of Indian emigrants settled in the area soon after World War II ended [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenicity testing and VCG analysis, however, are laborious and time consuming. Disease development is also influenced by the environment, while VCG analysis requires the availability of (Bentley et al 1998;Lodwig et al 1999;Mostert et al 2017;Karangwa et al 2017). The markers developed in this study, therefore, present a valuable tool that can be used to speed up the identification of Foc Lineage VI strains and to guide the management of banana Fusarium wilt in ECA.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, isolates consisting of one particular AG or subgroup had a similar banding pattern, although they represented different geographical regions, host plants, or pathogenicity. Moreover, Lodwig et al (1999) showed that although clonal lineages of Fusarium oxysporum were not separated using total protein profiles analysed by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE), two isolates were distinguishable. Mohammadi et al (2003) used total soluble protein profiles and isozyme analysis to measure the genetic diversity of the Iranian R. solani isolate AG1.…”
Section: Introductionmentioning
confidence: 99%